Makna Sila Ke-4 dalam Diri Peserta Didik di Mentawai - Muslim, Muslim; Azizah, Cici Nur; Nursi, Nursi; Srimadona, Ade (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The indication of students who uphold the values ​​of Pancasila is having steadfastness and confidence in a nation which can be seen from the attitude of nationalism and love for the homeland which is born in the form of the 4th principle of the people's attitude which is led by wisdom in deliberation/representation which means being able to following the dynamics in actualizing the values ​​of Pancasila in the life of the nation and state. This research aims to determine the application of students' democratic attitudes as a manifestation of the 4th principle value through Civics subjects at SMA N 2 Sikakap and explore how the 4th principle is implemented in school. The research method used is qualitative with a case study design. Data collection techniques through observation, interviews, documentation and literature. Research data sources consist of primary and secondary sources. The results of the research show that students at SMA N 2 Sikakap show that PPKn subjects make a contribution to students so that students are able to understand the values ​​of Pancasila, are able to understand the principles of democracy and are able to appreciate the diversity and tolerance that exist in the Sikakap area accordingly. with the principles of the 4th principle and being a socializer in the social environment.